2011
DOI: 10.1002/hipo.20816
|View full text |Cite
|
Sign up to set email alerts
|

Selective tuning of hippocampal oscillations by phasic locus coeruleus activation in awake male rats

Abstract: Theta and gamma oscillations are thought to provide signal sets that promote neural coding of cognitive processes. Over 40 yrs ago, Jeffrey Gray reported event-related changes in a narrow band of hippocampal theta (7.5-8.5 Hz) which appeared to involve norepinephrine (NE) release from, the noradrenergic nucleus, the locus coeruleus (LC). These event-related alterations in EEG were elicited by novelty, attentional changes, the use of preparatory signals, and signal-mismatch events. Gray et al. have since provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 55 publications
(71 reference statements)
0
37
0
Order By: Relevance
“…16 2014]. This has already been suggested by C. Harley who found that activation of LC neurons by local glutamate infusion 'selectively tunes' hippocampal theta oscillations and reduces the frequency of the gamma oscillation [46,47]. Such actions of NE on oscillatory rhythms in cortex and hippocampus could well be the mechanism by which the LC-NE system 'resets' network activity.…”
Section: Locus Coeruleus Activity Is Phase Locked To Forebrain Oscillmentioning
confidence: 83%
“…16 2014]. This has already been suggested by C. Harley who found that activation of LC neurons by local glutamate infusion 'selectively tunes' hippocampal theta oscillations and reduces the frequency of the gamma oscillation [46,47]. Such actions of NE on oscillatory rhythms in cortex and hippocampus could well be the mechanism by which the LC-NE system 'resets' network activity.…”
Section: Locus Coeruleus Activity Is Phase Locked To Forebrain Oscillmentioning
confidence: 83%
“…We know for one that LC activation is followed by an increase in theta power parallel to the LTP in rodents [72]. On the other hand, no LTP was observed when gamma frequencies are ameliorated after LC activation [72].…”
Section: Memory Priming By Locus Coeruleus Activationmentioning
confidence: 99%
“…We know for one that LC activation is followed by an increase in theta power parallel to the LTP in rodents [72]. On the other hand, no LTP was observed when gamma frequencies are ameliorated after LC activation [72]. LC-facilitated CA1 LTD in rats is accompanied by the transient suppression of theta frequencies [27], which suggests that a theta frequency increase or suppression after LC activation might be responsible for directing synaptic plasticity (LTP or LTD) and forming subsequent memories.…”
Section: Memory Priming By Locus Coeruleus Activationmentioning
confidence: 99%
See 2 more Smart Citations